Punching and broaching combos - a newstamping tool - Mello,Lizandro B. de (2006)
The crescent searches for the reduction in time production are a factor that stimulates the improvement of the existent manufacturing techniques (Von Steeg 2002 and Waurzyniak 2002). Nowadays, the new researched processes should make possible the fabrication of pieces in a smaller time with a better use of the material resources and equipments (Klein 2002). The present work has for objective to show the viability of a combined tool that makes possible to perform a punching followed by a broaching in only one operation. This combo allies the advantages of the forming processes production and machining in only one process for heavy duty jobs on thick metal sheets. In this work were tested different configurations of combined punches. The objective was to analyze which are the main parameters that can have influence on the useful life of the tool in this new process, i.e., diameter of the punches and geometric form of the teeth for broaching. The precision overall depth of the holes, the roughness and the level of metal chip generation were measured. The analysis of the obtained data showed that the process is viable once were obtained holes with superior quality to the conventional stamping processes.